Evidência de tradicionalidade de uso de plantas medicinais: proposta de metodologia para o desenvolvimento de fitoterápicos para tratamento de feridas no Brasil - Leticia Mendes Ricardo (2017)
Drug development, according to modern science, uses rigorous testing methods, including clinical trials. On the other hand, the World Health Organization (WHO) recognizes the potential of traditional medicinal plants for drug development, and recommends that new sources of evidence should be used to assess their effectiveness and safety. According to WHO, the traditional secular and safe use of a medicinal plant can subsidize its clinical use, nowadays. The tradition use of medicinal plants is rich in Brazil, including those from the Amerindian culture described since the arrival of the first Europeans to the continent. The traditional use of a plant is an indicative of its effectiveness and safety, also for ANVISA, which has now accepted the registration of traditional herbal products. Wound care is an example of traditional practice with medicinal plants, as it is portrayed in documents on ancient civilizations and has been always an analysis theme to define the best treatment strategy. The objective of this study was to search for evidence of the traditional use of native medicinal plants in Brazil, especially those used in the treatment of wounds. In the first part of this study it was evaluated the traditional use of Brazilian species described in six editions of the book "Formulary and Medical Guide", by the physician Pedro Chernoviz and published between 1864 and 1920. A second part was directed to the search for evidences of traditionality use of barks of barbatimão and oil-resin of copaíba in the treatment of wounds, in bibliography published between 1576 and 2011. For the definition of the most important traditional uses, a methodology was developed in which the books were classified using weights, considering the publication date and the source of data. So, it was possible to calculate the score of each category of medicinal use based on the books weights and the frequency of citation. The book "Formulary and Medical Guide" cites 238 species and 117 traditional uses, comprising 36 used specifically to treat wounds and others general skin conditions. The secular and actual use of barks of barbatimão and oil-resin of copaiba to treat wounds was confirmed based on the historic bibliographic research.The most frequent use of barbatimão is like astringent, whereas copaíba had as main traditional use the healing of skin and mucosal lesions. The continuous use of products prepared with the plants, especially by health professionals, is also an indicative of the effectiveness and safety of the plants. The set of results confirm that Brazil´s native plant species also have traditionality, capable of subsidizing their clinical use, as recommended by WHO. Preparations containing barbatimão barks and copaiba oil-resin can be considered effective for use in the treatment of wounds. However, new actions are need to contribute to the improvement of the quality of the formulas for application of the products.